Robust substrate profiling method reveals striking differences in specificities of serum and lung fluid proteases - Douglas S. Watson; Kalyani Jambunathan; David S. Askew; Krishna Kodukula; Amit K. Galande (BioTechniques)
Proteases are candidate biomarkers and therapeutic targets for many diseases. Sensitive and robust techniques are needed to quantify proteolytic activities within the complex biological milieu. We hypothesized that a combinatorial protease substrate library could be used effectively to identify similarities and differences between serum and bronchoalveolar lavage fluid (BALF), two body fluids that are clinically important for developing targeted therapies and diagnostics. We used a concise library of fluorogenic probes to map the protease substrate specificities of serum and BALF from guinea pigs. Differences in the proteolytic fingerprints of the two fluids were striking: serum proteases cleaved substrates containing cationic residues and proline, whereas BALF proteases cleaved substrates containing aliphatic and aromatic residues. Notably, cleavage of proline-containing substrates dominated all other protease activities in both human and guinea pig serum. This substrate profiling approach provides a foundation for quantitative comparisons of protease specificities between complex biological samples.